Formulation of Cinchona Extract (Cinchona succirubra) Cream and The Safety as Hair Fertilizer - Hariyanti Hariyanti; Retno Wahyuningrum; Shintia Lintang Charisma (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Background: cinchona extract contains quinoline alkaloids, has telangiectatic activity, is practically insoluble in water so penetration into hair follicles is low and requires a delivery system, namely cream. Objective: to determine the formula of cinchona extract cream with good activity, physical stability and safety. Methodology: cinchona bark extraction (soxhletation method), phytochemical screening, cinchona extract dosage determination, optimization of cream formula using Design Expert software version 11. Evaluation: pH, adhesion, spreadability, viscosity and cycling test stability. Activity test using guinea pigs (Cavia porcellus) for 14 days, parameters of hair length/2 days, hair mass (14th day). Acute dermal irritation test using rabbit (Orycogalus cuniculus) by erythema and edema index parameters. Results: cinchona extract (13.32% yield) contained quinoline alkaloids, cinchona extract dosage was 20% (p<0.05). The optimum formula is F2 with characteristics: pH 6.48±0.07, adhesion 1.16±0.07, spreadability 4.99±0.85 and viscosity 3067±416.45, has good physical stability. Activity test: test area hair length 13.54 – 62.14% longer than normal control and 10.10 – 49.17% than negative control. The hair mass of test area was 122.91% heavier than normal control and 104.48% of negative control (p<0.05). Cinchona extract and excipients were non-irritant. Conclusion: Cinchona extract cream (20%) has hair fertilizer activity, good physical stability and safety.